Educação a distância - TV escola e PROINFO: impactos em escolas públicas do Estado do Rio de Janeiro - Marques, Maria Bernadeth Abreu (1999)
The distance education acquires power as more a kindl of learning and as a new resource of support to pedagogical work. B y this reason, there is a great government effort, in sense to emphasizes new kinds of distance Iearning. Follow the public political evolution of distance learning, essentially the perceived impacts in the learning quality, is the principal purpose of this study. This search was developped in Niteroi’s public schools, where the SEED programs' evolution were observed as others actions described in this work. Considering the up-to-date of the theme, it was indispensable, besides the literature review and the usual bibliographie indications, bases the author's argumention with periodicals and others knowledges through mediated information as the internet. The dissertation highlights all investigation result and concludes that all technologies and other forms of learning at a distanee were offered as updated resources, but they had been yet refused by the scholar community. The programs TV Escola e Proinfo would revolutionize the way teachers and students Iearn, but they did not change training and self-directed learning. The programs aims were not reach and the effort did not meet with much success.